The history, current state and future possibilities of the non-invasive brain computer interfaces - Frederico Caiado; Arkadiy Ukolov (Medicine in Novel Technology and Devices)
This study explores the history and current state of Brain-Computer Interfaces (BCIs), focusing on non-invasive, EEG-based devices. BCIs have evolved from early studies in neurophysiology to real-world applications that convert brain impulses into executable commands. The study discusses the two main categories of BCIs: invasive and non-invasive, highlighting their benefits and limitations. Invasive BCIs provide precise signals but carry higher risks and ethical concerns, while non-invasive BCIs are safer but face challenges with signal deterioration and external noise. The study also evaluates the potential of wider use and availability of non-invasive interfaces by analysing their existing capabilities, limits, and potential future developments. Solutions to overcome technological and ethical challenges are explored to improve usability, user experience, and impact in areas such as healthcare, rehabilitation, entertainment, and cognitive enhancement.